THE WORK OF BUUDAYBEK SABYR UULU AS A FOLKLORE COLLECTOR - Zhumashova N. A.; Tilekova N. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
This article examines the 50-year creative career of Buudaybek Sabyr uulu, dedicated to preserving and studying the oral traditions, musical compositions, and culture of the Kyrgyz people. He made a significant contribution as a collector, researcher, poet, translator, and scholar, standing among the foremost figures who left an invaluable legacy for Kyrgyz folklore and culture. When exploring the cultural heritage of any nation, we see that such treasures have their creators. However, the collectors and researchers who documented and preserved this heritage for future generations are often mentioned only briefly. Buudaybek Sabyr uulu’s diligence and sincerity, his high moral standards, humility, inner richness, wisdom, humanity, and thirst for knowledge are highly commendable. The rich legacy he left serves as an invaluable example for future generations.